Barsine paraprominens sp. nov. (Lepidoptera, Erebidae, Arctiinae, Lithosiini) from China, with notes on four new records - Huang, Si-Yao; Ji, Shu-Qin; Wang, Min; Fan, Xiao-Ling (Zootaxa, 2018)
New information of the genus Barsine Walker, 1854 is provided. A new species, Barsine paraprominens Huang & Wang sp. nov. is described from Pailong, SE Xizang. Four species: B. pseudomactans Volynkin & Černý, 2016, B. anomala (Elwes, 1890), B. pseudocardinalis Volynkin & Černý, 2017 and B. ustrina Černý, 2009 are recorded as new to China. The female genitalia of B. ustrina are described for the first time. Adults and genitalia of all species mentioned are illustrated.